Basic Statistics using Excel 2007 for use with: Basic Statistics for Business & Economics and Statistical Techniques in business & Economics - A. Lind Douglas (Mc Graw Hill Irwin, 2008)
Basic Statistics using excel 2007 is a workbook, which empowers students to use the computer to help them understand and apply the basic tools taght in an introductory statistics course. When students use excel to experiment and illustrate their problem, they can better visualize them and more easily see what happens.